Fulminant blast crisis with de novo 11q23 rearrangement in a Philadelphia-positive CML patient undergoing treatment with dasatinib. Issue 6 (December 2019) - Janjetovic, Snjezana; Asemissen, Anne Marie; Dicker, Frank; Binder, Mascha; Dierlamm, Judith; Bokemeyer, Carsten; Schafhausen, Philippe
Background: Progression of chronic myeloid leukemia (CML) is frequently accompanied by cytogenetic evolution, with an extra copy of the Philadelphia chromosome, trisomy 8 and 19, and isochromosome (17p) commonly detected. Translocations involving 11q23 chromosomal region have been rarely reported in CML. The few reported patients with blast crisis (BC) of CML carrying an 11q rearrangement have insufficient responses to tyrosine kinase inhibitors (TKIs) and possess a poor prognosis. Case report: We report the case of a 30-year-old man with CML who had a fulminant myeloid BC 4 months after initiation of first-line therapy with the TKI dasatinib, despite showing an optimal response at the 3-month timepoint. Despite cytoreductive therapy with hydroxyurea and 3rd-generation TKI ponatinib, the patient died within 10 days after the diagnosis of BC. Cytogenetic analyses revealed additional genetic aberrations including trisomy 8 and t(9;11)(p21;q23) involving the mixed lineage leukemia ( MLL ) gene. Conclusion: The presence of 11q23 rearrangements in the relapse clone in BC of CML most likely accounts for the adverse clinical outcome. Thus, in the case of rapid and unexpected BC, the presence of 11q rearrangements should be tested together with other additional chromosomal alterations, and immediate addition of chemotherapy to the TKIs should be evaluated.